Human pluripotent stem cell-derived acinar/ductal organoids generate human pancreas upon orthotopic transplantation and allow disease modelling. Issue 3 (15th September 2016) - Hohwieler, Meike; Illing, Anett; Hermann, Patrick C; Mayer, Tobias; Stockmann, Marianne; Perkhofer, Lukas; Eiseler, Tim; Antony, Justin S; Müller, Martin; Renz, Susanne; Kuo, Chao-Chung; Lin, Qiong; et al.
Abstract : Objective: The generation of acinar and ductal cells from human pluripotent stem cells (PSCs) is a poorly studied process, although various diseases arise from this compartment. Design: We designed a straightforward approach to direct human PSCs towards pancreatic organoids resembling acinar and ductal progeny. Results: Extensive phenotyping of the organoids not only shows the appropriate marker profile but also ultrastructural, global gene expression and functional hallmarks of the human pancreas in the dish. Upon orthotopic transplantation into immunodeficient mice, these organoids form normal pancreatic ducts and acinar tissue resembling fetal human pancreas without evidence of tumour formation or transformation. Finally, we implemented this unique phenotyping tool as a model to study the pancreatic facets of cystic fibrosis (CF). For the first time, we provide evidence that in vitro, but also in our xenograft transplantation assay, pancreatic commitment occurs generally unhindered in CF. Importantly, cystic fibrosis transmembrane conductance regulator (CFTR) activation in mutated pancreatic organoids not only mirrors the CF phenotype in functional assays but also at a global expression level. We also conducted a scalable proof-of-concept screen in CF pancreatic organoids using a set of CFTR correctors and activators, and established an mRNA-mediated gene therapy approach in CF organoids. Conclusions: Taken together, our platform provides novel opportunities to model pancreatic disease and development, screen for disease-rescuing agents and to test therapeutic procedures.